Step-by-step explanation:
After the raise, his pay is:
62000 + 0.05×62000
62000 (1 + 0.05)
65100
His pay after one year is $65,100.
To calculate Carlos's new salary after a 5% raise on his initial $62,000 salary, you multiply $62,000 by 0.05 to find the raise amount of $3,100, and then add it to the initial salary, resulting in a new salary of $65,100.
The question involves calculating the new salary of Carlos after a 5% raise following his initial year of employment. Carlos's starting salary is $62,000 per year. After one year, he receives a 5% raise. To calculate Carlos's new salary, follow this step:
Find the raise amount by calculating 5% of the initial salary. This can be found by multiplying the initial salary by 0.05 (which is the decimal form of 5%).Add the raise amount to the initial salary to find the new salary after one year.Now, let's do the math:
Raise amount = $62,000 times 0.05 = $3,100.New salary = Initial salary + Raise amount = $62,000 + $3,100 = $65,100.Therefore, after a 5% raise, Carlos's new annual pay will be $65,100.
Oscar gained x pounds within the last year. he weighed 96 pounds last year. which expressions correctly describes his current weight?
a. 96 - x
b. 96 + x
c. 96x
d. 96/x
Answer:
b
becasue to find his current weight you would use what you know and the amount of lbs he added (represented as x)
96 + x
Step-by-step explanation:
What is the greatest common factor of the polynomial 40x^7+135x^4+5x^4
5x^4
Step-by-step explanation:
simply we take 5x^4 bec. it can be divided by 40 and 135
Inverse of f(x)=3x-4
Answer:
[tex]\large\boxed{f^{-1}(x)=\dfrac{x+4}{3}=\dfrac{1}{3}x+\dfrac{4}{3}}[/tex]
Step-by-step explanation:
[tex]f(x)=3x-4\to y=3x-4\\\\\text{exchange x to y and vice versa}\\\\x=3y-4\\\\\text{solve for y}\\\\3y-4=x\qquad\text{add 4 to both sides}\\\\3y=x+4\qquad\text{divide both sides by 3}\\\\y=\dfrac{x+4}{3}[/tex]
what is the midpoint of the verticle line segment graphed below?
Answer:
C (2, -5/2)
Step-by-step explanation:
To find the midpoint of two points
mid = (x1+x2)/2, (y1+y2)/2
= (2+2)/2, (4+-9)/2
= 4/2, -5/2
=2,-5/2
Find the value of -36+(-9)+14+(-31)-(-66)
Answer:
4
Step-by-step explanation:
-36-9+14-31+66
=4
Since + - = - and - - = +
In the triangle, BC is the length of the mid-segment. Find the length of DE.
05.07) The net of a pyramid is shown below: The net of a square based pyramid, with bases labeled 7 inches and the height of the triangle labeled 14 inches. The surface area of the solid is ____ square inches. Numerical Answers Expected!
Answer: 245 [tex]in^{2}[/tex]
Step-by-step explanation:
You can find the Surface Area of a figure by adding up the areas of each shape.
First you have to find the area of the base.
7×7 = 49
Then you can find the area of the 4 triangles that complete the pyramid.
Formula for area of a triangle: [tex]\frac{1}{2} bh[/tex] (one half of base times height)
[tex]\frac{1}{2} (14*7) = x\\\frac{1}{2} 98 = x\\x = 49[/tex]
Since all the triangles are the same, you only have to calculate that once.
Now you just add everything together, and that's your surface area.
[tex]49+49+49+49+49= 245[/tex]
Please mark brainly if it helped you out!~
Answer: 245
Step-by-step explanation:
first you have to 7 for the square which = 14
then after that you do 1/2 b x h = 1/2 7 x 14= 3.5 x 14= 49 but then you have 4 triangles so 49 x 4=196. Then 49 + 196= 245
What is the solution
Answer:
y ≥ 14.
Step-by-step explanation:
y - 27 ≥ -13 Add 27 to both sides:
y ≥ 14 (answer).
For this case we must find the solution of the following inequality:
[tex]y-27 \geq-13[/tex]
We must add 27 to both sides of the inequality:
[tex]y \geq-13 + 27[/tex]
We know that different signs are subtracted and the sign of the major is placed.[tex]y \geq14[/tex]
So, the solution is [tex]y \geq14[/tex]
Answer:
Option C
Ir x represents a postive
number, select all expressions
whose valve is greater than X.
A.(1 - 1-4)x
B.(1 + 1/4)x
C. 7/8x
D. 9/8x
Answer:
I think it may be B, but double check
Answer:
B and D
Step-by-step explanation:
Considering the multiple choices and let us assume that x = 2,
Option A would be equal to [tex]\frac{3}{4}x[/tex],
so if x = 2, then;
[tex]\frac{3}{4}x[/tex] = 1.5 (which is less than x)
Option B would give [tex]\frac{5}{4} x[/tex],
so if x = 2, then;
[tex]\frac{5}{4} x[/tex] = 2.5 ( which is greater than x)
From option C,
[tex]\frac{7}{8} x[/tex] = 1.75 (which is less than x)
From option D,
[tex]\frac{9}{8} x[/tex] = 2.25 ( which is greater than x)
So, options B and D are expressions whose values are greater than x.
A single, six-sided die is rolled. Find the probability of rolling an even
number or a number less than 3
Answer:
5/6 (if including 3) 4/6 (not including 3)
Step-by-step explanation:
1 and 2 are less than 3
4 and 6 are even
that leaves 5 and 3.
so 4 of the numbers are even or less than 3
Probability of rolling even number or number less than 3 is 2/3.
What is probability?Probability is defined by the possibility of the event to happen which is ratio of no. of favorable outcomes and the total no. of outcomes.
Probability of event = P(E) = No. of favorable outcomes/Total No. of outcomes
Here given that the dice is fair and six-sided is rolled.
Total no. of outcomes by rolling the dice=6 i.e. {1,2,3,4,5,6}
No. of favorable outcomes of getting even no. =3 i.e. {2,4,6)
Probability of rolling an even no.=P(even)= No. of favorable outcomes/Total No. of outcomes = 3/6
No. of favorable outcomes of getting no. less than 3 =2 i.e. {1,2}
Probability of rolling no. less than 3=P(<3) =No. of favorable outcomes/Total No. of outcomes = 2/6
No. of favorable outcomes of getting even no and number less than 3 =1 i.e. {2}
Probability of rolling an even no. and no. less than 3 =P(even and <3) = P(even ∩ <3)= No. of favorable outcomes/Total No. of outcomes = 1/6
As we know P(A∪B)=P(A)+P(B)-P(A∩B)
Probability of rolling an even no.or no. less than 3 = P(even or <3) = P(even ∪ <3)= P(even)+P(<3)-P(even ∩ <3)
=(3/6)+(2/6)-(1/6)
=4/6
=2/3
Therefore probability of rolling even number or number less than 3 is 2/3.
Learn more about probability
here: https://brainly.com/question/14192140
#SPJ2
You deposit $5000 in an account earning 8% interest compounded monthly. How much will you have in the account in 15 years?
[tex]\bf ~~~~~~ \textit{Compound Interest Earned Amount} \\\\ A=P\left(1+\frac{r}{n}\right)^{nt} \quad \begin{cases} A=\textit{accumulated amount}\\ P=\textit{original amount deposited}\dotfill &\$5000\\ r=rate\to 8\%\to \frac{8}{100}\dotfill &0.08\\ n= \begin{array}{llll} \textit{times it compounds per year}\\ \textit{monthly, thus twelve} \end{array}\dotfill &12\\ t=years\dotfill &15 \end{cases}[/tex]
[tex]\bf A=5000\left(1+\frac{0.08}{12}\right)^{12\cdot 15}\implies A=5000(1.00\overline{66})^{180}\implies A\approx 16534.61[/tex]
if f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)
Answer:
(f-g)(x) = x-3
Step-by-step explanation:
Given
f(x) = 3x-2
and
g(x) = 2x+1
We have to find (f-g)(x)
So,
(f-g)(x) = f(x)-g(x)
= 3x-2 - (2x+1)
= 3x-2-2x-1
=x-3
Hence,
(f-g)(x) = x-3
Answer:
( f - g ) ( x ) = x - 3
Step-by-step explanation:
We are to find [tex] ( f - g ) ( x ) [/tex] given that [tex] f ( x ) = 3 x - 2 [/tex] and [tex] g ( x ) = 2 x + 1 [/tex].
So basically we have to subtract the function g from function f.
[tex] ( f - g ) ( x ) = f(x) - g(x) [/tex]
Substituting the given functions in the above equation to get:
[tex] ( f - g ) ( x ) = (3x - 2) - (2 x + 1 ) [/tex]
[tex] ( f - g ) ( x ) = 3x - 2 - 2 x - 1 [/tex]
[tex] ( f - g ) ( x ) = 3x - 2 x - 2 - 1 [/tex]
[tex] ( f - g ) ( x ) = x - 3 [/tex]
The sales of a certain product after an initial release can be found by the equation s=12 sqrt (4t) + 10 , where s represents the total sales (in thousands) and t represents the time in weeks after release. Make a table of values, graph the function and use the graph to estimate the sales 12 weeks after release.
Check the picture below.
Step-by-step explanation:
Given : The sales of a certain product after an initial release can be found by the equation [tex]s=12\sqrt{4t}+ 10[/tex], where s represents the total sales (in thousands) and t represents the time in weeks after release.
To find : Make a table of values, graph the function and use the graph to estimate the sales 12 weeks after release ?
Solution :
The equation [tex]s=12\sqrt{4t}+ 10[/tex]
where, s represents the total sales (in thousands) and t represents the time in weeks after release.
We put t=1,2,3,.....,12 and create a table
t [tex]s=12\sqrt{4t}+ 10[/tex]
1 34
2 43.94
3 51.56
4 58
5 63.66
6 68.78
7 73.49
8 77.88
9 82
10 85.89
11 89.59
12 93.13
Find BC please in the picture
B. 25 Km. The measure of BC is 25 km.
The easiest way to solve this problem is using the cosine theorem c = √a²+b²-2ab*cos A.
BC = √AC²+AB²-2(AC)(AB)*cos A
BC = √(21km)²+(14km)²-2(21km)(14km)*cos 89°
BC = √441km²+196km²-588km²*(0.017)
BC =√637km²-10.26km²
BC = √636.74km²
BC = 25.03km ≅ 25
There is a total of 270 men women and children on a train the ratio of men to women is 4:5 the ratio of women to children is 10:9 how many men are on the train
Answer:
80
Step-by-step explanation:
Let's say M is the number of men, W is the number of women, and C is the number of children.
M + W + C = 270
M/W = 4/5
W/C = 10/9
We have three equations and three variables, so we can solve this. Let's use substitution.
W = 5/4 M
C = 9/10 W
Substitute into the first equation:
M + 5/4 M + 9/10 W = 270
Substitute again:
M + 5/4 M + 9/10 (5/4 M) = 270
Solve:
M + 5/4 M + 9/8 M = 270
8/8 M + 10/8 M + 9/8 M = 270
27/8 M = 270
M = 80
There are 80 men on the train.
whats the are of this figure?!?
Answer:
The area is 5.5 cm squared.
Step-by-step explanation:
To find the area, you have to find the areas of the rectangle and the triangle separately and then add your two values together.
The formula for the area of a rectangle is as follows:
[tex]A=lw[/tex]
In this formula, "l" refers to length and "w" refers to width.
As shown in the diagram, your length is 1.5 cm and your width is 2 cm.
Simply plug these numbers into the formula and simplify.
[tex]A=1.5*2\\A=3[/tex]
The area of the rectangle is 3 cm squared.
Next, find the area of the triangle. The formula for the area of a triangle is as follows:
[tex]A=\frac{1}{2} bh[/tex]
In this formula, "b" refers to the measure of the base and "h" refers to the measure of the height.
Your base (b) is 2 cm.
To find your height, subtract the length of the rectangle (1.5 cm) from the total length of the shape (4 cm). This will give you a height of 2.5 cm.
Next, plug your values into the formula and simplify.
[tex]A=\frac{1}{2} *2*2.5\\A=1*2.5\\A=2.5[/tex]
The area of the triangle is 2.5 cm squared.
Add the area of the rectangle (3 cm squared) to the area of the triangle (2.5 cm squared), and you have the area of the entire figure (5.5 cm squared).
Note: Carlos' mistake in the problem is that he forgot to subtract the length of the rectangle from the length of the entire shape, and incorrectly used 4 cm as his height for the triangle rather than 2.5 cm.
The cost function of an apple stand is C = 10n + 150, where n is the number of buckets of apples sold. The revenue function of this apple stand is r= 15n.
Create a graph to show each of these functions. According to your graph,
what is the break-even point for this apple stand?
A. n = 30
B. n = 10
C. n = 25
D. n = 14
Check the picture below.
Answer:
A. n = 30Step-by-step explanation:
The cost function is
[tex]C=10n+150[/tex]
Where [tex]n[/tex] is the number of buckets of apples sold.
The revenue is defined as
[tex]r=15n[/tex]
The image attached shows both functions graphed in the same coordinate system. According with the graph, the break-even point is at (30,450), that is, 30 of buckets sold and $450 of revenue and cost.
In other words, we need to sell 30 buckets to have the cost and revenue equals.
Therefore, the answer is A.
what is the sum f the first five termns of a geometric series with a_1=20 and r=1/4?
Answer:
1705/64
Step-by-step explanation:
A geometric series contains terms that are in the form [tex]a_1\cdot(r)^{n-1}[/tex] where [tex]a_1[/tex] is the first term and [tex]r[/tex] is common ratio.
A common ratio is the number that is used to find the next term by multiplying previous term by [tex]r[/tex].
Now we can use a formula and we would be using [tex]S_n=\frac{a_1(1-r^n)}{1-r}[/tex] where n is the number of terms you are adding and [tex]a_1[/tex] is the first term and r is the common ratio.
Before we do that, I'm going to do this without that formula. Sum means we are just going to add these terms after finding them.
The first term is 20.
The second term is (1/4)(20)=5.
Third term is (1/4)(5)=5/4.
Fourth term is (1/4)(5/4)=5/16.
The fifth term is (1/4)(5/16)=5/64.
Now we add them (20)+(5)+(5/4)+(5/16)+(5/64)
Putting this into the calculator gives me: 1705/64.
Now let's do the formula way as well.
Again we have:
r=1/4
[tex]a_1=20[/tex]
n=5 since we adding the first 5 terms:
[tex]S_5=\frac{20(1-(\frac{1}{4})^5}{1-\frac{1}{4}}[/tex]
[tex]S_5=\frac{20(1-\frac{1}{1024}){\frac{3}{4}}[/tex]
[tex]S_5=\frac{20-\frac{20}{1024}}{\frac{3}{4}}[/tex]
Dividing by 3/4 is the same as multiply by 4/3.
[tex]S_5=(20-\frac{20}{1024})\frac{4}{3}[/tex]
[tex]S_5=20 \cdot \frac{4}{3}-\frac{20}{1024}\cdot\frac{4}{3}[/tex]
[tex]S_5=\frac{80}{3}-\frac{5}{256} \cdot \frac{4}{3}[/tex]
[tex]S_5=\frac{80}{3}-\frac{20}{256 \cdot 3}[/tex]
[tex]S_5=\frac{80}{3}-\frac{5}{64 \cdot 3}[/tex]
[tex]S_5=\frac{80}{3}-\frac{5}{192}[/tex]
Multiplying first fraction by 64/64:
[tex]S_5=\frac{80(64)}{3(64)}-\frac{5}{192}[/tex]
[tex]S_5=\frac{5120}{192}-\frac{5}{192}[/tex]
{tex]S_5=\frac{5115}{192}[/tex]
Dividing to and bottom by 3:
[tex]S_5=\frac{1705}{64}[/tex].
Find the value of expression m(m-n) for m=3 and n=1
I need the ANSWER ASAP
Answer:
6
Step-by-step explanation:
m = 3
n = 1
Equation
m(m - n) Substitute the givens
Solution
3(3 -1 ) Evaluate what is inside the brackets.
3(2) multiply
6
Answer:
m=3 and n-1 ,find m2- mn
Step-by-step explanation:
which of the following is a factor of 6x^3 + 6?
a) x - 1
b) x + 1
c) x² - 2x + 1
d) x² + x + 1
Answer:
B
Step-by-step explanation:
Given
6x³ + 6 ← factor out 6 from each term
= 6(x³ + 1)
x³ + 1 is a sum of cubes and factors as
x³ + 1 = (x + 1)(x² - x + 1)
Hence
6x³ + 6 = 6(x + 1)(x² - x + 1)
With factor (x + 1) → B
Answer:
b) x + 1
Step-by-step explanation:
you can either
1) take (6x³ + 6) and divide by all the choices to see which one gives you a factor. You will realize that if you divide this by option b, you will be able to factorize the equation as follows:
(6x³ + 6) = 6(x+1)(x²−x+1)
Hence option b is a factor
or
2) (my preferred method), utilize the properties of functions and roots.
Let function f(x) = 6x³ + 6
any value of a which gives f(a) = 0 is a root , i.e (x-a) is a factor.
In this case, lets consider option b
let x + 1 = 0 -------> or x = -1
substitute this into the function f(x)
f(-1) = 6 (-1)³ + 6
f(-1) = -6 + 6 = 0
hence x = -1 is a root , or (x+1) is a factor.
as a sanity check, lets try choice a) x -1
let x - 1 = 0 -------> or x = +1
substitute this into the function f(x)
f(1) = 6 (1)³ + 6
f(1) = 6 + 6 = 12 ≠0
hence x = 1 is NOT a root , or (x-1) is NOT a factor.
You can do the same for c and d and find that they too are NOT factors.
Find the value of a in the picture
Answer:
The measure of arc a is 86°
Step-by-step explanation:
we know that
The measure of the inner angle is the semi-sum of the arcs comprising it and its opposite.
so
86°=(1/2)[arc c+arc a]
see the attached figure with letters to better understand the problem
In this problem
Triangles ABO and CDO are congruent by SSS postulate theorem
∠AOB=∠COD
∠AOB=arc a -----> by central angle
∠COD=arc c -----> by central angle
therefore
The measure of arc a is congruent with the measure of arc c
arc a=arc c
so
86°=(1/2)[2arc a]
86°=[arc a]
arc a=86°
What are the solutions of the equation x4 - 9x2 + 8 = 0? Use u substitution to solve.
A. x = 1 and x = 2sqrt2
B. x=+/-1 and x = +/-2sqrt2
C. x=+/-i and x = +/-2isqrt5
D. x = +/-i and x=2sqrt2
Answer:
[tex]\large\boxed{B.\ x=\pm1\ and\ x=\pm2\sqrt2}[/tex]
Step-by-step explanation:
[tex]x^4-9x^2+8=0\\\\x^{2\cdot2}-9x^2+8=0\qquad\text{use}\ (a^n)^m=a^{nm}\\\\(x^2)^2-9x^2+8=0\\\\\text{substitute}\ x^2=t\geq0\\\\t^2-9t+8=0\\\\t^2-t-8t+8=0\\\\t(t-1)-8(t-1)=0\\\\(t-1)(t-8)+0\iff t-1=0\ \vee\ t-8=0\\\\t-1=0\qquad\text{add 1 to both sides}\\t=1\geq0\\\\t-8=0\qquad\text{add 8 to both sides}\\t=8\geq0[/tex]
[tex]t=x^2\to x^2=1\ \vee\ x^2=8\\\\x^2=1\Rightarrow x=\pm\sqrt1\to x=\pm1\\\\x^2=8\Rightarrow x=\pm\sqrt8\to x=\pm\sqrt{4\cdot2}\to x=\pm\sqrt4\cdot\sqrt2\to x=\pm2\sqrt2[/tex]
Answer:
Step-by-step explanation:
Given is the equation of 4th degree in x,
[tex]x^4 - 9x^2 + 8 = 0[/tex]
Substitute [tex]x^2=u[/tex]
[tex]u^2-9u+8=0\\(u-1)(u-8)=0[/tex]
u=1 and u =8
i.e. [tex]x^2=1\\x^2 =8[/tex]
Solving we get
[tex]x=1,-1,2\sqrt{2}, -2\sqrt{2}[/tex]
Option B is right.
Sally is near the end of a three year lease on a car with an original MSRP of $38,000. Her leasing company claims that the car is now worth only $28,500. Which percentage represents the residual value of Sally’s leased car?
a.
25%
b.
33%
c.
67%
d.
75%
Answer:
Option D is correct.
Step-by-step explanation:
Original Price of car = $38,000
Current Price of car = $28,500
The residual value of Sally's leased car = x = ?
Residual value * Original Price = Current Price
x * 38,000 = 28,500
x = 28,500/38,000
x = 0.75
Since we need to find percentage
Multiply the residual value with 100 i.e,
0.75 * 100 = 75%
Option D is correct.
Enter a recursive rule for the geometric sequence.
2,−6,18,−54,...
Answer:
[tex]a_n=-3a_{n-1}[/tex] where [tex]a_1=2[/tex]
Step-by-step explanation:
Recursive means you want to define a sequence in terms of other terms of your sequence.
The common ratio is what term divided by previous term equals.
The common ratio here is -6/2=18/-6=-54/18=-3.
Or in terms of the nth and previous term we could say:
[tex]\frac{a_n}{a_{n-1}}=r[/tex]
where r is -3
[tex]\frac{a_n}{a_{n-1}}=-3[/tex]
Multiply both sides by the a_(n-1).
[tex]a_n=-3a_{n-1}[/tex] where [tex]a_1=2[/tex]
Answer:
see explanation
Step-by-step explanation:
A recursive rule allows us to obtain any term in the sequence from the previous term.
These are the terms of a geometric sequence with common ratio r
r = - 6 ÷ 2 = 18 ÷ - 6 = - 54 ÷ 18 = - 3
Thus to obtain a term in the sequence multiply the previous term by - 3
[tex]a_{n+1}[/tex] = - 3 [tex]a_{n}[/tex] with a₁ = 2
The figure shows two similar triangles:
Which two sets of angles are corresponding angles?
Osvoldo has a goal of getting at least 30%, percent of his grams of carbohydrates each day from whole grains. Today, he ate 220 grams of carbohydrates, and 55grams were from whole grains.
Did Osvoldo meet his goal? How many grams of whole grain did he eat?
Answer:
Osvoldo does not meet his goal
He had to have eaten at least 66 grams of whole grains to meet his goal.
Step-by-step explanation:
step 1
Find out the 30% of the grams of carbohydrates that Osvoldo ate today
Remember that
30%=30/100=0.30
so
0.30(220)=66 grams
step 2
Compare the 30% of the grams of carbohydrates that Osvoldo ate today with the 55 grams of whole grains
we know that
To Osvoldo meet his goal the 55 grams of whole grain must be greater than or equal to the 30% of the grams of carbohydrates that Osvoldo ate today
55 < 66
therefore
Osvoldo does not meet his goal
He had to have eaten at least 66 grams of whole grains to meet his goal.
Lela purchased three mechanical pencils and a notebook that cost five dollars per purchase totaled $11 how much was each pencil use P to represent the cost of each pencil
Answer: 3p+5=11
Step-by-step explanation:
3p+5=11
-5 -5
3p=6
3p/3=6/3
P=2
$2
The cost of each pencil is $2.
What is a word problem?A word problem is a verbal description of a problem situation. It consists of few sentences describing a 'real-life' scenario where a problem needs to be solved by way of a mathematical calculation.
For the given situation,
Number of pencils = 3
Number of notebook = 1
Cost of a notebook = $5
Total cost = $11
Let number of pencil be p.
Lela purchased three mechanical pencils and a notebook is
⇒ [tex]3p+5=11[/tex]
⇒ [tex]3p=11-5[/tex]
⇒ [tex]3p=6[/tex]
⇒ [tex]p=\frac{6}{3}[/tex]
⇒ [tex]p=2[/tex]
Hence we can conclude that the cost of each pencil is $2.
Learn more about word problems here
brainly.com/question/20594903
#SPJ2
please answer this.
Also if you can, please answer my other question its very simmilar
For this case we have that a percentage equivalent to[tex]\frac {1} {8}[/tex]is given by:
[tex]x = \frac {1} {8} * 100 =[/tex] 12.5%
Then, according to the steps, it is observed that Harriet made an incorrect division, deboa multiply. So, the second step is the wrong one.
Answer:
Option B
Complete the square to solve the equation below x^2 + 10x - 13 = 17
Answer:
x = -12.42 or x = 2.42
Step-by-step explanation:
x^2 + 10x - 13 = 17
To solve this using the completing the square method, we will follow the steps below;
First, we will add 13 to both side of the equation, we want only the x variable to be on the left-hand side of the equation
x^2 + 10x - 13 + 13 = 17 + 13
x^2 + 10x = 30
The next step is to add both-side of the equation by square of half of the coefficient of x (that is ; half of 10 is 5, then we will add 5² to both-side of the equation)
x^2 + 10x + 5² = 30 + 5²
Then we can now factorize the left-hand side of the equation and at the same time simplify the right-hand side of the equation
(x + 5)² = 30 + 25
(x + 5)² = 55
We will then take the square root of both-side of the equation
√(x + 5)² = ±√55
x + 5 = ±√55
To get the value of x, we will subtract 5 from both-side of the equation
x + 5 - 5 = ±√55 - 5
x = ±√55 - 5
Either x = + √55 -5 = 7.42 -5 = 2.42
OR
x = -√55 - 5 = -7.42 - 5 = -12.42
Therefore either x = -12.42 or x = 2.42
x = -12.42 or 2.42
1. Meghan has to cover only the lateral surface of a cylindrical container of height
12.9 in. and radius 13.6 in. with fabric. To the nearest square unit, calculate how
much fabric does she need? Use a calculator.
A 1,713 in.2
B 2,264 in.2
c 1,102 in.2
OD 1,683 in.2
Answer:
Option C [tex]1,102\ in^{2}[/tex]
Step-by-step explanation:
we know that
The lateral surface area of a cylinder is equal to
[tex]LA=2\pi rh[/tex]
we have
[tex]r=13.6\ in[/tex]
[tex]h=12.9\ in[/tex]
assume
[tex]\pi =3.14[/tex]
substitute
[tex]LA=2(3.14)(13.6)(12.9)[/tex]
[tex]LA=1,101.76\ in^{2}[/tex]
Round to the nearest square inch
[tex]LA=1,102\ in^{2}[/tex]